2021
DOI: 10.1016/j.dam.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing claw-free subcubic graphs and 4-chordal subcubic graphs

Abstract: Hoffmann-Ostenhof's Conjecture states that the edge set of every connected cubic graph can be decomposed into a spanning tree, a matching and a 2-regular subgraph. In this paper, we show that the conjecture holds for claw-free subcubic graphs and 4-chordal subcubic graphs. induced subgraph isomorphic to K 1,3 . A cycle is called chordless if it has no chord. A graph G is called chordal if every cycle of G of length greater than 3 has a chord and a graph is 4-chordal if it has no induced cycle of length greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…We recall that a graph is claw-free if it contains no induced copy of K 1,3 . As mentioned before, the 3DC has been verified for claw-free cubic graphs [1,15]. Using an idea similar to the one used by Aboomahigir, Ahanjideh and Akbari [1], one can show that the 2DC also holds for claw-free graphs.…”
Section: Claim 2 G Contains No Parallel Edgesmentioning
confidence: 55%
See 2 more Smart Citations
“…We recall that a graph is claw-free if it contains no induced copy of K 1,3 . As mentioned before, the 3DC has been verified for claw-free cubic graphs [1,15]. Using an idea similar to the one used by Aboomahigir, Ahanjideh and Akbari [1], one can show that the 2DC also holds for claw-free graphs.…”
Section: Claim 2 G Contains No Parallel Edgesmentioning
confidence: 55%
“…As mentioned before, the 3DC has been verified for claw-free cubic graphs [1,15]. Using an idea similar to the one used by Aboomahigir, Ahanjideh and Akbari [1], one can show that the 2DC also holds for claw-free graphs. For completeness, we provide its proof below.…”
Section: Claim 2 G Contains No Parallel Edgesmentioning
confidence: 55%
See 1 more Smart Citation
“…The former of these results was extended to all connected plane cubic graphs by Hoffmann-Ostenhof, Kaiser, and Ozeki [8] in 2018. In the same year it was also proved to hold for claw-free (sub)cubic graphs by Aboomahigir, Ahanjideh, and Akbari [9] as well as by Hong et al [10]. More recently, Lyngsie and Merker [11] showed that weakening the matching requirement to allow for paths of length 2 suffices to make the conjecture true and Heinrich [12] verified it for 3-connected cubic graphs of tree-width 3.…”
Section: Introductionmentioning
confidence: 94%
“…In the same year it was also proved to hold for claw-free (sub)cubic graphs by Aboomahigir, Ahanjideh, and Akbari [8]. More recently, Lyngsie and Merker [9] showed that weakening the matching requirement to allow for paths of length 2 suffices to make the conjecture true and Heinrich [10] proved the conjecture for 3-connected cubic graphs of tree-width 3.…”
Section: Introductionmentioning
confidence: 98%